Simulation platform for 5G systems - Santos, Bruno Alexandre Amaro (2020)
Thanks to the technological advances in communications, it has never been so fast and simple to communicate with people anywhere in the world, as well as enjoying a variety of services, only by using a mobile phone with internet access. But the increasing number of users and features requires an ever-demanding design of wireless communication systems, with the constant need to increase speed and efficiency in information transmission. A new generation of wireless communication systems that will revolutionize the way we share information is currently emerging, promising a significant increase in transmission rates. This generation presents itself as 5G. In order to optimize the bandwidth usage, current 4G systems already use a signal modulation technique called OFDM, and future 5G systems will also make use of this technique. Despite having optimum spectral performance, OFDM modulation has a high signal Peak-to-Average Power Ratio (PAPR), which can cause the power amplifiers to operate in a non-linear zone. This may compromise the electrical efficiency of the system and increase the probability of error in information transmission. To evaluate the performance of wireless communication systems against the distortions caused by the amplification of OFDM signals, a simulation platform was developed. In this platform are included laboratory measurements for two types of amplifiers in different operating environments that are typical in 5G systems. In order to understand how different system characteristics differently affect its performance, signals with two distinct bandwidths are tested for three digital signal modulation techniques. The tests also consider the effects of the wireless channel as well as schemes of multi-antenna systems.